Pengaruh Variabel Pengambilan dan Pengolahan Darah terhadap Kualitas Hematologis Packed Red Cells (PRC) - Dwi Eni Danarsih; Nurpuji Mumpuni (Poltekkes Kemenkes Semarang, 2026)
This study aimed to analyze the relationship between blood bag type, blood collection duration, and processing time with the quality of Packed Red Cells (PRC) to support transfusion safety. An observational analytic study with a cross-sectional design was conducted at the Blood Transfusion Unit of PMI Bantul. A total of 50 PRC units collected from male voluntary donors were analyzed. Variables included blood collection duration, processing delay, blood bag type, and processing method, while PRC quality was assessed based on hemoglobin concentration, hematocrit, and physical appearance. Data were analyzed using Spearman correlation and Mann–Whitney tests. The results showed that blood collection duration and processing delay had no significant effect on PRC hemoglobin levels. However, both factors demonstrated a significant negative correlation with PRC hematocrit, indicating that longer collection and delayed processing reduced hematocrit values. Processing method significantly affected hematocrit, with centrifugation producing higher hematocrit compared to sedimentation, while blood bag type showed no significant influence. All PRC units met quality standards with clear plasma and no clot formation. This study highlights the importance of timely blood processing and appropriate processing methods to maintain PRC quality, thereby contributing to improved transfusion safety and blood bank quality management.